Hyperbaric oxygenation and the genic expression related to oxidative stress in the heart of mice during intestinal ischemia and reperfusion - Somaio Neto,Frederico (2017)
Abstract Purpose: To investigate the effects of hyperbaric oxygenation (HBO) on intestinal ischemia and reperfusion (IR) injury, we evaluated the expression of 84 genes related to oxidative stress and the antioxidant response in mouse hearts. Methods: Four groups were subjected to 60 minutes of intestinal ischemia followed by 60 minutes of reperfusion: IRG, ischemia and reperfusion group without HBO; HBO-IG, which received HBO during ischemia; HBO-RG, which received HBO during reperfusion; and HBO-IRG, which received HBO during ischemia and reperfusion. The control group (CG) underwent anesthesia and laparotomy and was observed for 120 minutes. The (RT-qPCR) method was applied. Genes with expression levels three times below or above the threshold cycle were considered significantly hypoexpressed or hyperexpressed, respectively (Student’s t-test p<0.05). Results: Eight genes (9.52%) were hyperexpressed in the IRG. When the HBO groups were compared to the IRG, we found a decrease in the expression of eight genes in the HBO-IG, five genes in the HBO-RG, and seven genes in the HBO-IRG. Conclusion: The reduction in the expression of genes related to oxidative stress and antioxidant defense following HBO in mouse hearts resulting from intestinal IR injury was more favorable during the ischemic period than during the reperfusion period.